WAYS OF MANIFESTATION OF THE AUTHOR-CHARACTER IN CONTEMPORARY DRAMA (Proceedings of Southern Federal University. Philology, 2022)
DOI 10.18522/1995-0640-2022-3-119-128In the contemporary drama, that is, plays written in recent decades, the voice of the author is becoming more and more distinguishable. It occurs not only in the title, the list of characters, remarks and other elements of the paratext, as it was before, but also directly in the text. In new plays, playwrights often bring out a character who is close to them, real people, with the facts of his biography, views on life, and so on (let’s call him the author-character). In the article, we consider how the author-character relates to the representations of the “image of the author” in a work of art, how it manifests itself in contemporary drama, and how the relationship between the author and the reader / viewer is built in the text. Plays written from 1991 to 2021 were selected as material — “Cherepakha Manya” (“Manya the Turtle”) by Nikolai Kolyada, “Khozyain kofeyni” (“Coffee House Owner”) by Pavel Pryazhko, “Zapis’ preryvayetsya” (“The Recording Is Interrupted”) by Elina Petrova and “Plotnik” (“The Carpenter”) by Lidia Golovanova.Key words: author, author’s image, author’s presence, contemporary drama